Factors affecting tax payment through commercial bank system of enterpreneurs in Xay district, Oudomxay province - SINGTHALANON, Vanlisack; CHANTHAVONE, Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purposes of the study were: 1) to investigate factors affecting tax payment through the commercial bank system; and 2) to study the problems of tax payment through the commercial bank system of entrepreneurs in Xay district (Oudomxay province). The research sample was 240 people from Legal entity entrepreneurs, collected using questionnaires as the data collection instrument, and the statistics used for data analysis were frequency, percentage, mean, and standard deviation. Multiple linear regression was used to analyze cross-sectional data for the study. In addition, interview a tax officer about the problem of tax payment through the business banking system of entrepreneurs in Xay district (Oudomxay province). The results found that the factors of tax payment through the commercial bank system of entrepreneurs in Xay district (Oudomxay province) were at a very important level (4.18 and S.D. = 0.56), and the factors of tax payment through the commercial bank system of entrepreneurs in Xay district (Oudomxay province) were at an extremely important level (4.44 and S.D. = 0.62). The factors affecting tax payment through the commercial bank system of entrepreneurs in Xay district (Oudomxay province) consist of five factors such as online trust, technological infrastructure, tax filing regulations, attitude, and perceived risk. These factors have a positive relationship with tax payment through the commercial bank system of entrepreneurs in Xay district (Oudomxay province) at a significant level of 0.05. The level of problems in tax payment through the commercial bank system in Xay district (Oudomxay province) was at a moderate level (2.79 and S.D. =0.91) and consisted of problems such as the lack of knowledge about tax laws, the lack of knowledge and understanding of tax filing and tax payment through the commercial bank system, the error side during system filing, being afraid to be checked later, and the complex approval and filing process.